Elemental Analysis of Anethum sowa L. (Dill) Root by XRF Spectrometry - Saleh-e-In, MM; Sultana, A; Hossain, MA; Ahsan, M; Roy, SK (Bangladesh Journal of Scientific and Industrial Research, 2011)
Anethum sowa L. (Dill) were collected from different places of Bangladesh and subjected to quantitative estimation of the elements present in roots of the herb. The elemental analyses were done by XRF (PW 2404 PANAlytical) method. The maximum percentage (%) of the elements found in the root samples were: 24.71, 24.43, 10.30, 9.21, 5.16, 5.11, 3.72, 3.46, 3.08, 2.36, 0.32 and 0.16 for K, Ca, Si, Na, Cl, Mg, Al, S, P, Fe, Ti and Mn respectively. Rb, Sr and Zr were present in small amount and Ni, Cu, Zn, Y and Ba were present in trace amount. However Co, Pb, As and Hg were not found in any of the samples under investigation. This analyses may be helpful for the use of Anethum sowa L. root in pharmaceutical preparation and in ayurvedic form of medicine. Keywords: Anethum sowa L; Dill; Elemental composition; XRF Spectrometry. DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9035 BJSIR 2011; 46(3): 307-312